(untitled) (The Review of Diabetic Studies, 2024)
Background: Cardiovascular illness is a prominent contributor to mortality, characterised by a lack of effective therapeutic interventions tailored to specific clinical requirements. Fibroblast growth factor 23 (FGF-23) is a protein hormone that was first characterised for its involvement in mineral metabolism. FGF-23 is mostly produced by osteocytes and has a pivotal function in suppressing the reabsorption of phosphate in the renal proximal convoluted tubule. The aim: Comparison between Cardiovascular Diseases in Patients With Type 2 Diabetes and without DM regarding serum level of FGF23. Study the relation between serum FGF23 level and insulin resistance in Cardiovascular Diseases in Patients With Type 2 Diabetes. Material and Method: The present study included 60 patients with Diabetes Mellitus (DM) with a mean age of 56.02±1.395 years and an age range of (40-80) years and 60 patients with cardiovascular diseases and diabetes (CVD and DM) with a mean age of 59.20±1.478 and an age range of (40-80) years, Who visited Al-Basrah Teaching Hospital in Basrah. in addition, the study included 60 healthy controls mean age of healthy control subjects was 54.72±1.405years. All patients in this study were diagnosed by specialized doctors and the diagnosis was verified by clinical and laboratory tests, during the period from September 2022 to September 2023. All Subjects signed a written informed consent form. The BMI was calculated as body weight (kg) and was divided by squared height in meters. Results: The results of this study showed an increase in the level of Triglycerides, Cholesterol, LDL Cholesterol and VLDL Cholesterol in CVD and DM patients as compared with DM and Control, while The results of this study showed a decrease in the level of HDL Cholesterol and there was a significant difference in concentrations among study groups (p-value <0.0001). Also, The results of this study showed an increase in the level of fibroblast growth factor 23 in CVD and DM patients as compared with DM and control and there was a significant difference in concentrations of FGF23 among study groups (p-value <0.0001). Conclusion: From this study, it could be concluded that FGF23, CRP, may be a clinically useful and simple index for predicting the concomitant presence of Cardiovascular Diseases insulin resistance and dysglycemia among apparently healthy, young (<50 years) Al-Basra populations.